The Curious Case of the Yen as a Safe Haven Currency : A Forensic Analysis - Botman, Dennis (IMF Working Papers; Working Paper ;, 2013)
During risk-off episodes, the yen is a safe haven currency and on average appreciates against the U.S. dollar. We investigate the proximate causes of yen risk-off appreciations. We find that neither capital inflows nor expectations of the future monetary policy stance can explain the yen's safe haven behavior. In contrast, we find evidence that changes in market participants' risk perceptions trigger derivatives trading, which in turn lead to changes in the spot exchange rate without capital flows. Specifically, we find that risk-off episodes coincide with forward hedging and reduced net short positions or a buildup of net long positions in yen. These empirical findings suggest that offshore and complex financial transactions should be part of spillover analyses and that the effectiveness of capital flow management measures or monetary policy coordination to address excessive exchange rate volatility might be limited in certain cases.